Kesenjangan Wacana Ekoteologi Dalam Buku Teks PAI Kelas XII: Studi Atas Absensnya Nilai-Nilai Konservasi Lingkungan - Ubaidillah; Naal Hira’ Angrheini (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The global climate crisis demands a progressive religious education response to instill ecological awareness (ecoteology) in students. This study aims to analyze the construction of ecotheological discourse or its absence in the Grade XII Islamic Religious Education and Character Building Textbook published by the Ministry of Education, Culture, Research, and Technology's Book Center (2022). Using a critical content analysis approach, this study traces the integration of key ecotheological concepts such as Tawhid, Khalifah, Ihsan, Fasad, and Mizan. The results indicate a null curriculum phenomenon (missing curriculum) related to environmental issues. Quantitatively, there is no explicit discussion of nature conservation as a religious mandate. Qualitatively, there is a significant dislocation of meaning in theological concepts. The term Khalifah appears 10 times but is limited to the context of political history and power, while the concept of Ihsan, which appears 46 times, is dominated by ritual and socio-humanitarian dimensions. Furthermore, the ecological postulates of Q.S. Al-Qasas: 77, which prohibits causing damage (fasad), has been reduced to merely moral damage within the context of work ethics, rather than ecological damage. This study concludes that the textbook remains trapped in an anthropocentric (human-centered) paradigm and ignores the importance of balance with nature. The absence of this discourse has implications for the breakdown of the character development chain of